1998
DOI: 10.1021/ma980405s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Volume Phase Transition in Poly(N-isopropylacrylamide-co-acrylic acid) Gels

Abstract: The shrinking/swelling behavior across the volume phase transition temperature, Tc, has been investigated for cylindrical gels made of poly(N-isopropylacrylamide-co-acrylic acid) (NIPA/AAc) and poly(N-isopropylacrylamide) (NIPA). NIPA/AAc gel shrank at Tc ) 43°C by quasistatic heating. On the other hand, the gel underwent a shrinking transition at a lower temperature, i.e., Tc ≈ 40°C, when a temperature jump was applied to the gel from 20°C. More interestingly, the shrinking process consisted of three stages: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 33 publications
2
93
0
Order By: Relevance
“…On the other hand, a rapidly shrinking gel tends to form a dense skin that inhibits water loss from the interior, slowing the volume change and possibly leading to fracture of the gel under the resulting shrinkage stresses. The effect of such skin formation on deswelling kinetics has been studied by Hirose and Shibayama, [112] who showed that pure NIPAM gels form a dense layer and shrink much more slowly than weakly charged copolymers of NIPAM and acrylic acid, which retain more mobility for water in the collapsed state.…”
Section: Thermally Driven Changesmentioning
confidence: 99%
“…On the other hand, a rapidly shrinking gel tends to form a dense skin that inhibits water loss from the interior, slowing the volume change and possibly leading to fracture of the gel under the resulting shrinkage stresses. The effect of such skin formation on deswelling kinetics has been studied by Hirose and Shibayama, [112] who showed that pure NIPAM gels form a dense layer and shrink much more slowly than weakly charged copolymers of NIPAM and acrylic acid, which retain more mobility for water in the collapsed state.…”
Section: Thermally Driven Changesmentioning
confidence: 99%
“…This type of approach addresses the problem that a rapidly shrinking gel tends to form a dense skin that inhibits water loss from the interior, both slowing the volume change and possibly leading to fracture of the gel under the resulting shrinkage stresses. The effect of such skin formation on deswelling kinetics has been studied by Hirose and Shibayama, who showed that pure NIPAM gels form a dense layer and shrink much more slowly than weakly charged copolymers of NIPAM and acrylic acid that retain more mobility for water in the collapsed state [98].…”
Section: Thermally Driven Gel Actuatorsmentioning
confidence: 99%
“…After the maximum in the m app curve at a temperature of 25.4 °C the deswelling of the PNIPAM governs the scene. This happens about 8 degrees below the LCST which is quite an astonishing result because so far, only moderate changes in the PNIPAM solution state have been described in this temperature range [24][25][26][27][28][29][30]. Moreover, 25 °C is frequently used as starting or reference temperature for deswelling studies [26,[29][30][31][32][33].…”
Section: Temperature Of the Water Poolmentioning
confidence: 99%